Analisis Yuridis Pelaksanaan Undang -Undang No 7 Tahun 2014 Terhadap Pergerakan Barang di Kota Batam - Ukas, Ukas; Jamba, Padrisan (Jurnal Jejak Hukum Indonesia (JHI), 2024)
Law No. 7 of 2014 concerning Trade, is a national development in the field of economic law that is compiled and implemented to realize general welfare through the implementation of economic democracy, with the principle of togetherness, in the perspective of the constitutional foundation. Indonesian national trade must reflect a series of economic activities that are compiled and implemented to realize welfare in social control for all Indonesian people. In the regulation and implementation of the Law in relation to the movement of goods and or services must reflect the progress of economic law development based on accountability, transparency, especially for business actors (traders in their buying and selling transactions and or in carrying out economic and trade activities in the midst of society. Thus, legal certainty, fairness, health, and security are created properly in accordance with the regulations of trade laws and several other related technical regulations.